Inherited Metabolic Causes of Stroke in Children: Mechanisms, Types, and Management - Tabarki, Brahim; Hakami, Wejdan; Alkhuraish, Nader; Graies-Tlili, Kalthoum; Nashabat, Marwan; Alfadhel, Majid (Frontiers in Neurology, 2021)
A stroke should be considered in cases of neurologic decompensation associated with inherited metabolic disorders. A resultant stroke could be a classical ischemic stroke (vascular stroke) or more commonly a “metabolic stroke.” A metabolic stroke begins with metabolic dysfunctions, usually caused by a stressor, and leads to the rapid onset of prolonged central neurological deficits in the absence of vessel occlusion or rupture. The cardinal features of a metabolic stroke are stroke-like episodes without the confirmation of ischemia in the typical vascular territories, such as that seen in classic thrombotic or embolic strokes. Identifying the underlying cause of a metabolic stroke is essential for prompt and appropriate treatment. This study reviews the major inherited metabolic disorders that predispose patients to pediatric stroke, with an emphasis on the underlying mechanisms, types, and management.